Palladium-Catalyzed Annulation of Internal Alkynes: Direct Access to π‑Conjugated Ullazines - Wan, Danyang; Li, Xiaoyu; Jiang, Ruyong; Feng, Boya; Lan, Jingbo; Wang, Ruilin; You, Jingsong (Organic letters, 2016)
A palladium-catalyzed cyclization reaction of 1-(2,6-dibromophenyl)-1H-pyrroles with alkynes has been developed to construct various π-conjugated indolizino[6,5,4,3-ija]quinolones (ullazines) with a reactive functional group tolerance. As illustrative examples, three new ullazine-based sensitizers are synthesized, and the performance of these dyes is examined in DSSC devices, which demonstrates the potential of direct C–H functionalization in the construction of organic optoelectronic materials.